2023
DOI: 10.1002/ejp.2075
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in the use of lumbar imaging, opioid analgesics and spinal surgery for low back pain: A systematic review and meta‐analysis

Abstract: Background and Objective: There is a substantial gap between evidence and clinical care for low back pain (LBP) worldwide despite recommendations of best practice specified in clinical practice guidelines. The aim of this systematic review was to identify disparities associated with race or ethnicity in the use of lumbar imaging, opioid analgesics, and spinal surgery in people with LBP. Databases and Data Treatment:We included observational studies which compared the use of lumbar imaging, opioid analgesics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…Research has shown the damaging effect of unconscious bias on healthcare assessment, test ordering, and treatment recommendations (Fitzgerald & Hurst, 2017). For example, racial bias has been shown to influence opioid prescription and surgical intervention in the management of LBP, though the authors were unable to determine the influence on imaging due to low certainty of evidence (Chen et al., 2023). In our review, we found many studies reporting that patient characteristics such as sex, socioeconomic status, and ethnicity influenced imaging CDM, suggesting potential biases.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown the damaging effect of unconscious bias on healthcare assessment, test ordering, and treatment recommendations (Fitzgerald & Hurst, 2017). For example, racial bias has been shown to influence opioid prescription and surgical intervention in the management of LBP, though the authors were unable to determine the influence on imaging due to low certainty of evidence (Chen et al., 2023). In our review, we found many studies reporting that patient characteristics such as sex, socioeconomic status, and ethnicity influenced imaging CDM, suggesting potential biases.…”
Section: Discussionmentioning
confidence: 99%